2016
DOI: 10.1111/pbr.12357
|View full text |Cite
|
Sign up to set email alerts
|

The restorer gene for soybean M‐type cytoplasmic male sterility, Rf‐m, is located in a PPR gene‐rich region on chromosome 16

Abstract: Over the past decade, M-type cytoplasmic male sterility (CMS) line W931A and a variety of restorer lines have been exploited for the release of hybrid seeds in soybean (Glycine max). However, the identities of restorer genes in the nuclei of soybean restorer lines are still unclear. In this study, we analysed the inheritance pattern of restorer locus Rf-m from restorer line WR016 and constructed a high-resolution map of this locus. Results showed that Rf-m in WR016 is a monogenic dominant gene located within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…PPR proteins are classified as Rf proteins that suppress CMS gene expression through posttranscriptional mechanisms such as editing, cleavage, and degradation of the target mRNAs in many plants such as rice, Brassica, radish, and sorghum (Chen et al 2014; Brown et al 2003; Hu et al 2012; Iwabuchi et al 1999; Jordan et al 2010; Kazama et al 2003). Recently, Wang et al (2016a) identified the Rf gene for soybean M-type CMS, Rf-m, which is located in a PPR gene-rich region on chromosome 16. This region contains 19 putative open reading frames (ORFs), and seven of them encode putative PPR proteins.…”
Section: Discussionmentioning
confidence: 99%
“…PPR proteins are classified as Rf proteins that suppress CMS gene expression through posttranscriptional mechanisms such as editing, cleavage, and degradation of the target mRNAs in many plants such as rice, Brassica, radish, and sorghum (Chen et al 2014; Brown et al 2003; Hu et al 2012; Iwabuchi et al 1999; Jordan et al 2010; Kazama et al 2003). Recently, Wang et al (2016a) identified the Rf gene for soybean M-type CMS, Rf-m, which is located in a PPR gene-rich region on chromosome 16. This region contains 19 putative open reading frames (ORFs), and seven of them encode putative PPR proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 94 sterile mutants were identified and three-line system-based CMS was also developed ( Ray et al, 2003 ; Palmer et al, 2012 ; Zhao et al, 2019 ; Nadeem et al, 2021 ). Along with these, three CMS restorer loci and two independent locus Rf-m were fine-mapped ( Wang et al, 2016 ; Zhao et al, 2019 ). Similarly, genes related to NMS have also been identified in soybean.…”
Section: Male Sterility and Its Mechanism In Soybeanmentioning
confidence: 99%
“…Three SSR markers, Satt684, Satt276 and Satt545 on LG “A1” linked to the rf ‐gene of M‐type CMS line (W931A), were obtained, and their genetic distances were 29.5, 10.7 and 14.1 cM, respectively (Tang, Zhang, Chen, Chen, & Liang, ). Further, Wang et al () mapped Rf ‐m located in a ~160‐kb region on LG “J”, a restorer gene from M‐type CMS lines, which was flanked on each side by GmSSR1602 and GmSSR1610 at a distance of 0.11 and 0.25 cM, respectively. Additionally to this, Wang et al () found that Satt215, Sctt011 and Satt547 on LG “J” linked to the rf ‐gene of JLCMS82A.…”
Section: Genetic Mechanism Of Male Sterility In Soybeanmentioning
confidence: 99%